Effectiveness and safety of levilimab in combination with methotrexate in treatment of patients with active rheumatoid arthritis resistant to methotrexate monotherapy (double-blinded randomized placebo controlled phase III clinical study SOLAR) - V. I. Mazurov; M. A. Korolev; A. M. Prystrom; E. V. Kunder; N. F. Soroka; A. A. Kastanayan; T. V. Povarova; T. V. Plaksina; O. V. Antipova; D. G. Kretchikova; S. A. Smakotina; O. A. Tciupa; et al. (Современная ревматология, 2021)
Levilimab is anti-interleukin-6 receptor (IL6R) monoclonal antibody. The article presents data obtained during 24 weeks of the SOLAR phase III study.Objective: to confirm efficacy and safety of levilimab in combination with methotrexate (MTX) in patients with methotrexate resistant active rheumatoid arthritis (RA).Patients and methods. 154 adult patients, aged ≥18 years with the diagnosis of RA (ACR/EULAR 2010) and confirmed disease activity at screening despite treatment with MTX for at least 12 weeks (in a stable dose 15-25 mg/week). Patients were randomized 2:1 in levilimab (162 mg once a week, subcutaneously) + MTX (n=102) or placebo + MTX (n=52) group.The hypothesis of superiority of levilimab over placebo was tested for two co-primary efficacy endpoints: proportion of subjects who achieved ACR20 at week 12 and proportion of subjects who achieved low disease activity (LDA) of RA (DAS28-CRP <3.2) at week 24. Safety was assessed through monitoring of adverse events (AEs).Results and discussion. Seventy (68.6%) subjects who received levilimab and 20 (38.5%) who received placebo achieved ACR20 response at week 12. Fifty three (52%) subjects who received levilimab and 3 (5,8%) subjects who received placebo achieved LDA at week 24. The most common adverse events (reported in ≥5% of subjects) in levilimab and placebo arms, respectively were (by decreasing frequency): blood c holesterol increase (24% vs 12%), alanine aminotransferase elevation (11% vs 8%), lymphocyte count decrease (9% vs 8%), blood total bilirubin increase (11% vs 0%), blood triglycerides increase (10% vs 2%), aspartate aminotransferase elevation (7% vs 4%), positive interferon-gamma release assay (IGRA) with M.tuberculosis antigen blood test (5% vs 6%), absolute neutrophil count decrease (8% vs 0%). No deaths were occurred.Conclusion. The study confirmed superior efficacy of levilimab + MTX over placebo + MTX in subjects with MTX resistant active RA. Levilimab showed favorable safety profile and low immunogenicity. No new important safety risks were detected.